Awareness of colorectal cancer signs and symptoms: a national cross-sectional study from Palestine - Mohamedraed Elshami; Mohammed Ayyad; Mohammed Alser; Ibrahim Al-Slaibi; Shoruq Ahmed Naji; Balqees Mustafa Mohamad; Wejdan Sudki Isleem; Adela Shurrab; Bashar Yaghi; Yahya Ayyash Qabaja; Fatima Khader Hmdan; Mohammad Fuad Dwikat; et al. (BMC, 2022)
Abstract Background In low-resource settings, the awareness level of colorectal cancer (CRC) signs and symptoms plays a crucial role in early detection and treatment. This study examined the public awareness level of CRC signs and symptoms in Palestine and investigated the factors associated with good awareness. Methods This was a national cross-sectional study conducted at hospitals, primary healthcare centers, and public spaces in 11 governorates across Palestine between July 2019 and March 2020. A translated-into-Arabic version of the validated bowel cancer awareness measure (BoCAM) was utilized to assess the awareness level of CRC signs and symptoms. For each correctly identified CRC sign/symptom, one point was given. The total score (ranging from 0 to 12) was calculated and categorized into three categories based on the number of symptoms recognized: poor (0 to 4), fair (5 to 8), and good awareness (9 to 12). Results Of 5254 approached, 4877 participants completed the questionnaire (response rate = 92.3%). A total of 4623 questionnaires were included in the analysis; 1923 were from the Gaza Strip and 2700 from the West Bank and Jerusalem (WBJ). Participants from the Gaza Strip were younger, gained lower monthly income, and had less chronic diseases than participants in the WBJ. The most frequently identified CRC sign/symptom was 'lump in the abdomen' while the least was 'pain in the back passage'. Only 1849 participants (40.0%, 95% CI: 39.0%-41.0%) had a good awareness level of CRC signs/symptoms. Participants living in the WBJ were more likely to have good awareness than participants living in the Gaza Strip (42.2% vs. 37.0%; p = 0.002). Knowing someone with cancer (OR = 1.37, 95% CI: 1.21-1.55; p < 0.001) and visiting hospitals (OR = 1.46, 95% CI: 1.25-1.70; p < 0.001) were both associated with higher likelihood of having good awareness. However, male gender (OR = 0.80, 95% CI: 0.68-0.94; p = 0.006) and following a vegetarian diet (OR = 0.59, 95% CI: 0.48-0.73; p < 0.001) were both associated with lower likelihood of having good awareness. Conclusion Less than half of the study participants had a good awareness level of CRC signs and symptoms. Future education interventions are needed to improve public awareness of CRC in Palestine.